Pengaruh Gaya Hidup, Citra Merek dan Harga Terhadap Keputusan Pembelian Smarthphone Merek Oppo: Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Malikussaleh - Ramadhan, Rizki .; Muchsin, Muchsin Muchsin; Heikal, Mohd . (Jurnal Visioner & Strategis, 2024)
This research aims to find out whether lifestyle, brand image and price influence the decision to purchase Oppo brand smartphones among Malikussaleh University students. The location of this research is at Malikussaleh University. The objects of this research are all Malikussalaeh University students who use Oppo smartphones. The population in this study were all students at Malikussalaeh University who used Oppo smartphones. The sampling method using accidental sampling was given to 102 respondents, namely students at Malikussalaeh University who used Oppo smartphones. The method used to support this research is a quantitative method and in this research is a multiple linear regression model using SPSS. The results of this research show that lifestyle variables, brand image and price have a partial and simultaneous influence on the decision to purchase an Oppo brand smartphone. The correlation coefficient (R) of 0.667 indicates that there is a fairly strong relationship between the independent variable and the dependent variable of 66.7%. The R2 value is 0.445, this shows that the influence of the independent variables, namely lifestyle, brand image and price on the decision to purchase an Oppo brand smartphone, is 44.5%, while the remaining 56.5% is explained by other variables outside this research. Keywords : Lifestyle, Brand Image, Price, Purchase Decisions